(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
More than one hundred thousand children are born each year with congenital clubfoot, or talipes equinovarus, mostly in low and middle-income countries (LMIC) where there are often deficiencies in access to health services. The overall burden of disease can be appreciated by adding these incident cases to the hundreds of thousands of cases that have not received treatment or have residual deformities following previous treatment. There are also numerous cases associated with syndromes and neuromuscular diseases, and also patients who have had a relapse after previous treatment including extensive surgical releases. While the disability due to a neglected or untreated clubfoot has not been quantified to our knowledge, consequences may include pain and/or reduced endurance during ambulation, calluses or skin breakdown from altered loading and shear stresses, and the inability to accommodate standard footwear. Perhaps the greatest disability may be rooted in the social stigma, children may be subject to verbal abuse, females may suffer more than males, and in some cultures a young lady may be unable to have an arranged marriage if she has an untreated clubfoot. Addressing the global burden of clubfoot is a multifaceted challenge. On one hand we need trained orthopaedic surgeons who are comfortable with a variety of procedures to provide technical solutions for individual patients. At the population level we need a public health approach in which systems for delivering the Ponseti method are developed and integrated within the health system, focusing on screening for early diagnosis, prompt referral for treatment, and adequate follow-up to address relapses and/or other concerns. It is clear that “one size does not fit all” when either caring for individual patients or organizing services to different regions of a country, contextually relevant solutions must be sought.